An algorithmic approach to the generation of non-developing musical structures - Reed, Sean (Trinity College (Dublin, Ireland). Department of Music, 2011)
It has been the goal of the author to develop an individual style of musical composition that reflects the personal tastes and convictions of the composer while maintaining relevance to contemporary, recent historical, and traditional issues surrounding not only music and art but also areas such as technology and philosophy
Keywords: Music, Ph.D.; Ph.D. Trinity College Dublin